Analisis Implementasi Manajemen Risiko Pada Pembiayaan Murabahah Di KSPPS BMT UB Amanah Laut Dendang - Salma Syahirah; Abdul Hadi Ismail (LPPM Universitas Labuhanbatu, 2025)
This research aims to find out in detail about matters concerning the implementation of risk management in murabahah financing, so that the implementation of risk management is carried out effectively and thoroughly at KSPPS BMT UB Amanah Laut Dendang. The research method used in this research is descriptive qualitative research method in the form of interviews with several sources. The results of the research in the form of interviews with BMT and customers can be said that the implementation of risk management needs to be carried out in Murabahah financing because there is bad financing found at BMT. This happens because do not conduct surveys on BMT customers so that they become the cause of bad financing so that it has an impact on customers who are not responsible for their dependents and many customers deliberately do not pay installments. Therefore, it is necessary to analyze the implementation of risk management on problematic Murabahah financing at BMT. The efforts that must be made by BMT in overcoming bad debts are by applying the 3R principle (Reschedulling, Reconditioning, Restructuring). In addition, BMT UB Amanah in handling risk management in murabahah financing has been carried out effectively. This is evidenced by all the efforts of BMT in minimizing the occurrence of risk management in murabahah financing in KSPPS BMT UB Amanah Laut Dendang.